Characterization of microstructures evolution on electrical responses of CaCu3Ti4O12 ceramics - Ab Rahman, Mohd Fariz; Hutagalung, Sabar Derita; Ahmad, Zainal Arifin; Ain, Mohd Fadzil; Mohamed, Julie Juliewatty (Elsevier, 2016)
CaCu3Ti4O12 (CCTO) ceramics was prepared by solid state method. The raw materials of CaCO3, CuO, and TiO2 were ball milled for 1 h. The mixed powders were calcined at 900 oC for 12 h. The phase formations of calcined powders were analyzed by using X-ray Diffraction (XRD). The calcined powders were pressed into pellet shape at 300 MPa and then were sintered at 1020, 1030 and 1040 oC for 10 h, respectively. The sintered samples were subjected to XRD, Scanning Electron Microscopy (SEM) and Impedance Analyzer for phase formation, microstructural and dielectric measurement analysis respectively. XRD analysis shows the presence of CCTO and secondary phases for the calcined powders. The samples sintered at 1020 and 1040 oC show the formation of CCTO phase with trace of secondary phases while complete formation of CCTO single phase was obtained for the sample sintered at 1030 oC. SEM analysis shows the phenomena of abnormal grain growth for the samples sintered at 1020 and 1040 oC while fine grain was observed for the sample sintered at 1030 oC. Sample sintered at 1040 oC was the densest sample while the sample sintered at 1020 oC had the highest percent of porosity. The highest dielectric constant (-3748) was achieved for samples sintered at 1040 oC while the lowest dielectric loss (-0.025) was obtained for the samples sintered at 1020 oC. These results indicate that sintering temperatures effectively changed the properties of CCTO.